Experimental investigation on NH3–H2O compression-assisted absorption heat pump (CAHP) for low temperature heating in colder conditions. (July 2016) - Wu, Wei; Wang, Baolong; Shang, Sheng; Shi, Wenxing; Li, Xianting
Highlights: A prototype of NH3 –H2 O compression-assisted absorption heat pump (CAHP) was built. For a generator inlet of 130 °C and an evaporator inlet of −5 to −25 °C, COP is 1.513–1.372. The lower limit of the evaporator inlet can be extended from −10 °C to −25 °C by CAHP. The heating capacity of absorption heat pump can be enhanced by approximately 55.5–85.0% by CAHP. The heating performance improved by CAHP is greater in much colder conditions. Abstract: The coefficient of performance (COP) and heating capacity of the absorption heat pump (AHP) decreased obviously as the evaporator inlet temperature dropped. Compression-assisted AHP (CAHP) could operate efficiently in colder conditions, and a prototype was constructed for experimental investigation. At a generator inlet of 130 °C, as the evaporator inlet decreases from −5 °C to −25 °C, the COP drops from 1.513 to 1.372, while the heating capacity deteriorates from 77.26 kW to 47.11 kW. Comparisons between CAHP and normal AHP indicated that CAHP can extend the lower limit of evaporator inlet temperature from −10 °C to −25 °C. Besides, CAHP can enhance the heating capacity by approximately 55.5–85.0% even when AHP can operate normally. Moreover, the improvement contributed by CAHP is greater under much colder conditions. The heating COP and capacity of CAHP are improved in all the conditions, while the primary energy efficiency is advantageous under lower evaporator inlet temperatures.